2016
DOI: 10.20944/preprints201609.0012.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of Impediments and Factors Affecting Waste Management: A Case of Accra Metropolis

Abstract: Solid waste management in Accra is a major challenge to the Metropolitan Authorities and inhabitants. The rapidly increasing population coupled with poor capacity of the municipal and private waste management companies to management waste effectively has created issues of environmental concern. Due to poor wastement managements systems, most household dispose waste discriminately leading to floods and health issues. The study showed that about 60% of household waste is organic materials which has the potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Source: (Fagariba & Song, 2017) The aim of the sustainable approach is to generate the minimum amount of waste possible, thereby minimizing the amount of waste that must be disposed in landfills.…”
Section: Fg 1 Comparison Of Waste Management Hierarchy (A) Traditionmentioning
confidence: 99%
“…Source: (Fagariba & Song, 2017) The aim of the sustainable approach is to generate the minimum amount of waste possible, thereby minimizing the amount of waste that must be disposed in landfills.…”
Section: Fg 1 Comparison Of Waste Management Hierarchy (A) Traditionmentioning
confidence: 99%
“…On the storage of wastes on the road meridian and by the road sides, majority of respondents 72.5% opined that it is a bad practice. Fagariba and Song [48], also concluded that inadequate access to these waste bins as one of the main barriers. Issues relating to environmental health and safety concern of residents show majority of residents close to central wastes storage are concerned about flies’ infestation with 63% respondents and follow by odour nuisance while aesthetic is the least of their concern.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, in Ngomongo Village of Korogocho informal settlement of Nairobi County, households without access to waste collection services dispose their waste by roadside dumping, burning and burying (Ochieng, 2016). A study by Fagariba and Song (2016) also found that in urban Accra, only 61% of households had access to waste collection services, the remaining 39% did not have access to waste collection services and dumped their wastes in bushes, holes, streets and gutters. Similarly, in Indian urban areas, waste collection is a challenge resulting in open dumping, which creates environmental and health hazards (Agarwal et al, 2015).…”
Section: Mochache M; Yegon R; Wakindiki Iicmentioning
confidence: 99%